Techno-economic Analysis on Grid-Connected Photovoltaic System (GCPV) in Mersing, Johor, Malaysia using Homer Simulation - Sufian bin Ramli, Mohd; Sufiah bte Abd Wahid, Siti; Amalina binti Zakaria, Noor; Najihah binti Abu Bakar, Nur; Kamarudin bin Hasan, Khairul; Azeehan binti Azli, Shakira (International Journal of Engineering and Technology, 2018)
Power generation relies heavily on fossil fuels such as coal, crude oil and natural gas to produce electricity. Fossil fuels are non-renewable which will eventually dwindle becoming too expensive. Therefore world nowadays are going towards sustainable renewable energy that are constantly replenished and will never run out. Malaysia also has introduced Feed-In Tariff (FiT) in order to promote and encourage consumer to shift towards renewable energy. Among all renewable energies available in Malaysia, solar photovoltaic (PV) is seen to be the most promising renewable energy in Malaysia. This paper presents the techno-economic analysis of a grid-connected photovoltaic (GCPV) system installation for a house in Mersing, Johor, Malaysia.Â  Techno-economic feasibility study is done using HOMER software. Design specifications of PV panels and inverters which include the size, type, cost and rating are selected based on the load profile and solar radiation data at Mersing. The result from GCPV system designed is the electricity export and import data obtained which then be analyzed to examine the feasibility of the system installed. FiT rates have been taken into account in the analysis. At the end of this paper, suitability of utilizing GCPV system in a house at Mersing, Johor, Malaysia has been discussed whereby the configuration with PV rating of 5kW and 5kW converter gives the optimum result with total NPC and COE of $2587 and $0.030/kWh respectively. In terms of economic analysis, with simulated payback period of 14 years, the total revenue of the optimum configuration exceeds initial capital cost with an amount of $1083 per year. Technically, 56% of electricity is generated from the PV array which equals to 6595kWh/yr. At FiT rate of RM0.7775/kWh, 33% of electricity production is sold to the grid with a total payment of RM238.24â„month.Â Â